Penanggulangan Tindak Pidana Korupsi, Kolusi Dan Nepotisme Dalam Pengadaan Barang Dan Jasa Pemerintah Di Provinsi Lampung - M. Gian Tantyo (Corruptio, 2020)
Government Goods and Services Procurement is a government spending mechanism that plays an important role in the utilization of the state budget. Government Goods and Services Procurement involves a very large amount of money, so the government is referred to as the biggest buyer in the country. In practice, in general the implementation of procurement of good / services of Government construction often results in problems, including violations both of the procedures for procurement of construction goods/services with improper conspiracy and violations that are detrimental to the State or related to criminal acts of corruption committed by construction goods/service procurement organization.The results of this study ultimately provide the answer that the causes of corruption, collusion and nepotism in the procurement of government goods and services in Lampung Province are 1) Very large funds poured out to turn the project into a powerful tempter to invite corruptors, 2) Large amount of data it turned out that it was complemented by the administration of unclear and closed government project plans. While efforts to tackle corruption, collusion and nepotism in the procurement of government goods and services in Lampung Province include: a) Preventive measures, in the form of: Supervision and Electronic Procurement (E-Procurenment) and b) Repressive Actions, namely: law enforcement with the application of law strict criminal sanctions.Suggestion from this research is that it should be formulated clearly about criminal liability in the implementation of government goods and services procurement of goods and services providers as well as on authorized officials in the implementation of government goods and services procurementGovernment Goods and Services Procurement is a government spending mechanism that plays an important role in the utilization of the state budget. Government Goods and Services Procurement involves a very large amount of money, so the government is referred to as the biggest buyer in the country. In practice, in general the implementation of procurement of good / services of Government construction often results in problems, including violations both of the procedures for procurement of construction goods/services with improper conspiracy and violations that are detrimental to the State or related to criminal acts of corruption committed by construction goods/service procurement organization.The results of this study ultimately provide the answer that the causes of corruption, collusion and nepotism in the procurement of government goods and services in Lampung Province are 1) Very large funds poured out to turn the project into a powerful tempter to invite corruptors, 2) Large amount of data it turned out that it was complemented by the administration of unclear and closed government project plans. While efforts to tackle corruption, collusion and nepotism in the procurement of government goods and services in Lampung Province include: a) Preventive measures, in the form of: Supervision and Electronic Procurement (E-Procurenment) and b) Repressive Actions, namely: law enforcement with the application of law strict criminal sanctions.Suggestion from this research is that it should be formulated clearly about criminal liability in the implementation of government goods and services procurement of goods and services providers as well as on authorized officials in the implementation of government goods and services procurement